The Feasibility of a Telehealth Exercise Program Aimed at Increasing Cardiorespiratory Fitness for People After Stroke - Margaret Galloway; Dianne L. Marsden; Robin Callister; Michael Nilsson; Kirk I. Erickson; Coralie English (International Journal of Telerehabilitation, 2019)
Background: Accessing suitable fitness programs post-stroke is difficult for many. The feasibility of telehealth delivery has not been previously reported.